Community knowledge, attitude, and perceived stigma of leprosy amongst community members living in Dhanusha and Parsa districts of Southern Central Nepal - Singh, Rakesh; Singh, Babita; Mahato, Sharika (PLOS Neglected Tropical Diseases, 2019)
Author summary Though Nepal declared leprosy to be no more a public health problem in 2010, its burden is constantly rising in Terai communities for the past 2 years with 3000 new leprosy cases being identified annually. With the fact that community’s knowledge and perception is important for prevention and control of leprosy this study aimed at assessing the community knowledge, attitude and stigma of leprosy amongst the community members living in Dhanusha and Parsa districts of Southern Central Nepal. The study was conducted in the communities of Dhanusha and Parsa by interviewing 423 individuals using structured questionnaire. All study respondents had heard about leprosy with main source of information to be health workers/hospital. A good proportion had myths such as bad blood/curse/heredity/bad deeds as the cause of leprosy and reported religious rituals as its treatment. Although more than half had good knowledge, only 2/5th had favorable attitude. The attitude was found to be influenced by knowledge. Also, knowledge, attitude and stigma score were found to be influenced by age, sex, ethnicity, religion, education and occupation. Strategizing the awareness programmes according to socio-demographic characteristics for enhancing the knowledge regarding leprosy cause, symptoms, transmission, prevention and treatment, could change the attitude to make it more favorable and thereby would help in reducing leprosy burden and enhancing the quality of life of leprosy patients.